Media Cetak dan Kualitas Guru - Witjaksana, Gunawan (Universitas Semarang, 2009)
The teacher must be professional, Teacher, to match with cose of Teachers and Lectures Law, must became profesional. There is many entry point to reach it, and for that goals, teachers had not reach with relax behaviour. But, the teachers must not became pesimistic, because many mass media give them many way to action, special for audience they give the public sphere for writing aspiration or opinion.The printing mass media have extra ordinary power to multiplier of knowledge, and to reach a lot of people. Of cource of that, the printer mass media, is the representative way for many teachers expression they aspiration and opinion.Congratulation, and maximizes that way to reach predicate the professional teachers at the fature.